2017
DOI: 10.3389/fnmol.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Clinical Utility of Non-coding RNAs in Epilepsy

Abstract: Epilepsy is a common neurologic disorder. The underlying pathological processes include synaptic strength, inflammation, ion channels, and apoptosis. Acting as epigenetic factors, non-coding RNAs (ncRNAs) participate in the regulation of pathophysiologic processes of epilepsy and are dysregulated during epileptogenesis. Aberrant expression of ncRNAs are observed in epilepsy patients and animal models of epilepsy. Furthermore, ncRNAs might also be used as biomarkers for diagnosis and the prognosis of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 105 publications
(135 reference statements)
0
27
0
Order By: Relevance
“…Looking for “circulating diagnostic miRNA in human epilepsy,” we found only 6 papers in PubMed (November 2017). To identify a reliable diagnostic biomarker able to identify the pathology, we analyzed those 6 publications 87 , 88 , 89 , 90 , 91 , 92 and the results are presented here ( Table 3 ).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking for “circulating diagnostic miRNA in human epilepsy,” we found only 6 papers in PubMed (November 2017). To identify a reliable diagnostic biomarker able to identify the pathology, we analyzed those 6 publications 87 , 88 , 89 , 90 , 91 , 92 and the results are presented here ( Table 3 ).…”
Section: Main Textmentioning
confidence: 99%
“…In the sixth paper, 92 a comparative analysis of circulating miRNAs in epilepsy has been proposed. In recent years, several miRNAs have been proposed as circulating biomarkers, showing dynamic changes of miRNA expression in relation to the history of the pathology.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported that miRNA levels in the circulating system were altered in correlation with certain pathological conditions, suggesting that circulating mi­RNA might become biomarkers for such diseases, including epilepsy [32, 46-49]. For example, in one genome-wide circulating miRNA expression profiling study, miR-106b-5p was found to have the best diagnostic value for epilepsy [50].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is also debated that miRNAs can have a nuclear function by modulating gene expression directly at the transcriptional level (reviewed by Catalanotto et al, 2016). Numerous miRNAs have been identified in relation to epilepsy pathogenesis (reviewed by Reschke and Henshall, 2015;Henshall et al, 2016;Shao and Chen, 2017;Tiwari et al, 2018), and also several ion channels appear to be under control of miRNAs, including K v 1.1, K v 4.2, Kcnk10 and Grin2a (Sosanya et al, 2013;Alsharafi et al, 2016;Gross et al, 2016;Haenisch et al, 2016;Tiwari et al, 2019; Table 1).…”
Section: Regulation Of Acquired Ion Channelopathies By Micrornasmentioning
confidence: 99%